2022
DOI: 10.1093/stmcls/sxab008
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive High Expression of NOXA Sensitizes Human Embryonic Stem Cells for Rapid Cell Death

Abstract: Human embryonic stem (hES) cells are highly sensitive to apoptotic stimuli such as DNA damage, which allows for rapid elimination of mutated cells during development. However, the mechanisms that maintain hES cells in the primed apoptotic state are not completely known. Key activators of apoptosis, the BH3-only proteins, are present at low levels in most cell types. In contrast, hES cells have constitutive high levels of the BH3-only protein, NOXA. We examined the importance of NOXA for enabling apoptosis in h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Our findings suggest that MCL-1 could regulate hPSC survival after exposure to 1% O 2 and that depending on the hypoxia inducer, alternative gene expression programs become operative in hPSCs. In line with our findings, it was demonstrated that high expression of NOXA sensitizes hPSCs for rapid cell death 53 . It is then conceivable that the decrease in the expression levels of MCL-1 triggered by 1% O 2 or the reduction of MCL-1/NOXA complexes due to S63845 treatment may turn hPSCs more susceptible to dye.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings suggest that MCL-1 could regulate hPSC survival after exposure to 1% O 2 and that depending on the hypoxia inducer, alternative gene expression programs become operative in hPSCs. In line with our findings, it was demonstrated that high expression of NOXA sensitizes hPSCs for rapid cell death 53 . It is then conceivable that the decrease in the expression levels of MCL-1 triggered by 1% O 2 or the reduction of MCL-1/NOXA complexes due to S63845 treatment may turn hPSCs more susceptible to dye.…”
Section: Discussionsupporting
confidence: 91%
“…PMAIP1 is essential for cell death in hESCs. It is highly expressed in pluripotent stem cells but decreases during neuronal differentiation and is controlled by POU5F1 (Basundra et al, 2022). SEPHS1 is essential for the survival of hESC.…”
Section: Resultsmentioning
confidence: 99%
“…PMAIP1 is essential for cell death in hESCs. It is highly expressed in pluripotent stem cells but decreases during neuronal differentiation and is controlled by POU5F1 (Basundra et al, 2022).…”
Section: Identification Of Hub Genes In Plurimlminetmentioning
confidence: 99%